Different Attacks and their Defense Line in Mobile Ad hoc Networks: A Survey - Gupta, P; Bansal, P (International Journal of Computer Sciences and Engineering, 2018)
Mobile Ad hoc Network (MANET) provides on the fly solution for those areas where wired network implementation is difficult. MANETs are network without infrastructure. They do not have central control. All nodes help each other in data communication. The life span of MANET is very small. The main features of MANET are: nodes are dynamic in nature resources availability in scarce and open channel. Due to resource scarcity some nodes may not provide their services to other nodes and some nodes may not participate in data transmission, to save their resources and they become selfish node. MANETs are susceptible for attacks. The open channel, resource scarcity and deployment type of network attract intruders for malicious activities. This survey paper has reviewed various articles from 1999 to 2018, in the view to look at how malicious nodes in a network make attacks on other nodes and what impact goes on network. Earlier work have been discussed about one or two types of attacks. This paper has studied and tried to bring all attacks under the one umbrella. The paper discussed these attacks in following categories: External and internal, active and passive, at protocol stack layer, security goals, attacks affecting routing. This paper also come along with defense line, have been proposed by various researchers for different attacks. Paper also tries to put attacks and their effect on one place. It includes type of attack, status of attacker, interaction, layer and security goals. It is suggested that what type of, defense, line of action should be taken, so that a network must sustain in adverse situation and available for its users.